The acceptance of RFID implementation to the manufacturers' supply chain environment / Farah Adila Abdul Ellah - Abdul Ellah, Farah Adila (2006)
Radio frequency identification (RFID) spending in Malaysia is estimated to grow at a compound annual growth rate (CAGR) of 45.84% to ahnost US$20.94 million (RM77 million) in 2010 from US$2.45 million ((RM9 million) in 2005. IDC in its latest research report on RFID, entitled "Malaysia RFID 2006-2010 Forecast and Analysis", said the bulk of spending would occur among the public sector (education and government ministries), and the manufacturing, financial services and healthcare sectors. The general purpose of this research is to capture the manufacturers' acceptance of RFID implementation to their supply chain environment. The objectives of this research can be defined as to determine the actual costs and that manufacturers willing to invest and increment of profit when introducing the RFID technology, to identify any significant business processes that need to be changed in managing the supply chain after the implementation of RFID technology and to identify the methodical approaches to RFID exploration that can help manufacturers to navigate the hazards and effectively explore the opportunities the technology holds. The implications of this study will be significance value to solutions providers and manufacturers of RFID in Malaysia.